1983
DOI: 10.1007/bf00239209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an artificial magnetic field on serotonin N-acetyltransferase activity and melatonin content of the rat pineal gland

Abstract: In the present study the effects of artificial magnetic fields on pineal serotonin-N-acetyltransferase (NAT) activity and melatonin content in male Sprague-Dawley rats were investigated to study the secretory activity of the pineal gland. Experimental inversion of the horizontal component of the natural magnetic field, performed at night-time, led to a significant decrease of both parameters investigated. During day-time, this effect was less conspicuous. During night-time, inversion of the horizontal componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(80 citation statements)
references
References 15 publications
5
73
1
1
Order By: Relevance
“…The magnetic field effect reported by Welker et al (1983) was confirmed by other researchers (Olcese et al, 1985;Olcese and Reuss, 1986). These studies used exposure facilities to rotate the earth's d-c magnetic field by 50 0 which increases field strength up to 1 G (more than double the ambient field).…”
Section: D-c Fields and Melatoninsupporting
confidence: 76%
See 1 more Smart Citation
“…The magnetic field effect reported by Welker et al (1983) was confirmed by other researchers (Olcese et al, 1985;Olcese and Reuss, 1986). These studies used exposure facilities to rotate the earth's d-c magnetic field by 50 0 which increases field strength up to 1 G (more than double the ambient field).…”
Section: D-c Fields and Melatoninsupporting
confidence: 76%
“…Welker et al (1983) reported that nocturnal melatonin and SNAT concentrations were quickly depressed in laboratory rats when the horizontal component of the earth's d-c magnetic field was inverted. They reported similar effects when the d-c magnetic field intensity was increased to twice the strength of the natural field.…”
Section: D-c Fields and Melatoninmentioning
confidence: 99%
“…Since the Semm et al (21) (24)(25)(26)(27), and AC magnetic fields (28)(29)(30). There have also been reports that such fields have little or no effect (31)(32)(33).…”
Section: Light Effects On Melatoninmentioning
confidence: 99%
“…Moreover, a reduced melatonin concentration has been reported post-magnetic field exposure (Welker et al, 1983), while the suppression of melatonin has been linked to various diseases, including cancer (reviewed in Hill et al, (2011)). Therefore the theory originally devised by Stevens (1987) proposing an ELF-MF associated nocturnal reduction in melatonin synthesis represents a tentative explanation as to the potential oncogenic action of magnetic fields (Wertheimer & Leeper, 1979).…”
Section: Mechanism 1131 the Melatonin Hypothesismentioning
confidence: 99%